Reuse of structural CLT elements: Assessing the impact of inter-element joint solutions on the reuse potential and environmental impact of a load-bearing wall panel - Ljunge, Jonna; Nerhed Silfverhjelm, Helena (My University, 2022)
The construction sector is a significant contributor to many of our current environmental challenges. To make the sector more sustainable, it is important to increase the use of renewable materials and implement circular strategies such as the reuse of building components. For reuse to become practically possible, the elements of a building must be easily removable without causing them damage. The joints connecting the building elements are thus vital for enabling reuse. The aim of this study is to assess how the choice of inter-element joint solution affects the reuse potential and environmental impact of reusing a load-bearing CLT wall panel. A literature review is performed to analyse how joint solutions impact the reuse potential of a structural element. The limited amount of existing research on the topic was found to be too general to be of sufficient relevance for CLT construction, in addition to being inconsistent in including important factors determining reuse potential. A new framework for analysing reuse potential is therefore developed in which joint solutions for a CLT wall panel are categorised according to the direction of removal they enable and whether their removal causes damage to a panel. The reuse potential framework is further used as a basis for developing scenarios for reusing a wall panel over multiple cycles. Two types of reuse are distinguished between in the scenarios: reuse between buildings (disassembly) and reuse within a building (adaption), forming the basis of an LCA of the environmental impact of multiple cycles. By analysing the direction of removal and potential damage caused to a panel, it is found that common joint solutions for CLT wall panels offer a range of reuse potential when assessed individually. However, there is currently a lack of joint combinations that fully enable reuse of a wall panel both through disassembly and adaption. To ensure more flexibility in how a panel can be reused, it is necessary to opt for other, or develop existing, solutions to increase the overall reuse potential. Additionally, the choice of joint solution affects the number of possible reuse iterations (use cycles) which is a key factor in determining the potential environmental impact reduction of a reused panel compared to the corresponding linear pathway. The largest impact reductions are found in the intermediate use cycles, suggesting that joint solutions enabling many intermediate cycles might create the largest reuse incentive.
Keywords: reuse, reuse potential, CLT, timber structure, joint, direction of removal, Design for Adaption, Design for Disassembly, circular economy, multiple-cycle LCA